Pulmonary dysfunction in children with beta thalassemia major in relation with iron overload - a cross sectional hospital based study - Boddu, A; Kumble, A; Mahalingam, S; Baliga, BS; Achappa, B (Asian Journal of Medical Sciences, 2015)
Background: Previously many patients with thalassemia major died from severe anemia during first decade, but with modern transfusion therapy many now survive beyond childhood. Because of such therapy, however excessive iron deposition occurs in lungs and causing respiratory dysfunction. Respiratory impairment occurs because of defective chelation and repeated transfusions. Objectives: To a) study pattern of respiratory impairment using spirometry, b) estimate iron overload by measuring serum ferritin levels, c) correlate a&b. Methodology:Thalassemia children >7year, on regular blood transfusion were included in the study after getting institutional ethical clearance .Standardised pulmonary function test was done using spirometry. Iron overload was assessed using serum ferritin levels. Severity of pulmonary dysfunction was correlated with serum ferritin levels. Results:Total of 42 children were included 62% were males and 38% were females (with median age 12yrs). By spirometry 95% had restrictive pattern of respiratory dysfunction. Mean ferritin value was 4152. Out of them10 (23.8%) mild, 25(59%) moderate and 5(12%) severe dysfunction based on FEV1 and FVC. The mean ferritin values in severe respiratory dysfunction is 6275 which is significantly higher when compared to moderate (4249) and mild (3066) pattern of respiratory dysfunction. None of the children had evidence of CCF. Significant correlation (p value=0.003) was found between severity of pulmonary dysfunction with ferritin values and also with weight of the child (p value=0.007). No other significant correlation found between severity pattern and transfusion index, age or height. Conclusion:Restrictive pattern is most common pulmonary dysfunction seen in chronic iron overloaded thalassemia major children. Regular blood transfusions with adequate chelation decrease incidence of pulmonary dysfunction. Screening of all thalassemia children using spirometry is need of the hour. DOI: http://dx.doi.org/10.3126/ajms.v6i5.11782 Asian Journal of Medical Sciences Vol.6(5) 2015 47-50